Manserockin legendat - Alatalo, Mikko; Hietanen, Pentti; Kankaanpää, Ari-Heikki; Koivisto, Rauli; Konttinen, Moog; Leskinen, Juice; Lindholm, Dave; Mustajärvi, Pate; Ruusukallio, Sami; Silvennoinen, Heikki; Syrjä, Aku; Syrjä, Martti; et al. (Mika Sundqvist, 1999)
20 kappaletta.